Affective Learning Model of Education Islamic Religious Education in Improving Character Building - ‘Azis, Muhammad Nasruddin; Wahono, Mohammad Rohman; Habiburrahman, Ahmad (Tahta Media Group, 2025)
This study aims to determine the implementation of the affective learning model of Islamic religious education in the formation of character building at the Baitul Qur'an Mlarak Islamic Boarding School (PAS: Pesantren Anak Sholeh), as well as its supporting and inhibiting factors. The method used is qualitative research, which produces descriptive data through observation and interviews with individuals involved in the learning process. The results show that the implementation of effective learning in MaIrasah Ibtidaiyah PAS is carried out through various habituations, such as reciting the Koran together, praying dhuhr and dhuhr in the congregation, and providing examples to students through shaking hands every morning. Supporting factors found include a good system of school activities, the competence of teachers who work together, and the willingness of students to excel. However, there are also inhibiting factors, such as the diverse backgrounds of students, the lack of cooperation between parents and teachers, and the different individual development of students. In conclusion, despite the challenges, the implementation of effective learning models in MI PAS shows positive results in shaping student character, with support from the school environment and student commitment, but further efforts are needed to overcome inhibiting factors so that learning can run more effectively and optimally.